The Effect of ROI and Exchange Rates on LQ45 Share Prices Through Profitability Empirical Studies in the Manufacturing Sector on the Indonesia Stock Exchange Period of 2016 to 2020 - Febrina Maya Yunida (Krisnadwipayana International Journal of Management Studies, 2023)
Today, in our global era, the rate of return on investment is a benchmark for companies in making business decisions, where the rate of return on investment is one of the factors for making these decisions. In addition, the exchange rate is another important factor to analyze in the manufacturing business world, because the exchange rate is closely related to purchase raw materials organizing from exports and imports. In addition, profitability is the company's measuring power in terms of getting profits. Besides that, the manufacturing companies contained in LQ45 are very dependent on the stock price which is the measuring power in making the company's management decisions. For this reason, this study aimed to determine the magnitude of the partial and simultaneous effect of ROI, exchange rate on stock prices including LQ45 in the manufacturing sector through profitability on the Indonesia Stock Exchange, where the level of influence between ROI, exchange rate on profitability is 0.741 or 74.1%, where there is a strong relationship between ROI, exchange rate on profitability. Then, the level of influence between ROI, the exchange rate on stock prices where the calculation results are 3.537 or 35.37%, namely there is a fairly strong relationship between ROI and the exchange rate on stock prices. Then, there is a strong relationship between profitability and stock price of 0.692 or 69.92%. Meanwhile, between ROI on stock prices through profitability where the direct influence of ROI on stock prices is greater than the indirect effect (3.290> 1.564) meaning that profitability is not an intervening variable in this study, as well as for the exchange rate on stock prices through profitability where the value of the direct effect is greater than the indirect effect (3.537> 1.222), which means that profitability is not an intervening variable in this study.